Research for Books on the Traditional Japanese Concepts of Nature. - Samuel, Edward (1993)
Keywords: dept.bio; faculty_collection; sabbatical_report

Manual of Ornithology: Avian Structure & Function - Proctor, Noble S.; Lynch, Patrick J. (Yale University Press, 1993)
Keywords: Anatomy; Birds; Laboratory manuals; dept.bio; faculty_collection

An introduction to issues of habitat fragmentation relative to transportation corridors with special reference to high-speed rail (HSR) - De Santo, R.S.; Smith, D.G. (Environmental Management, 1993)
Potential environmental impacts on wildlife result from siting and construction (short-term impacts) and habitat removal and fragmentation (long-term impacts) as a consequence of transportation corridor construction. Especially in rural districts, wildlife migration corridors and dispersal orientation are altered or destroyed and wildlife populations and their gene pools are isolated. This significantly weakens the wildlife community. Prudent selection of construction corridors reduces fragmentation impacts by maximizing preserved fragment sizes, and by running parallel to, not through, natural areas. Corridor width determines the degree to which wildlife movement is restricted except that culverts, underpasses, overpasses, and one-way gates, can aid wildlife in cross movements. Minimum underpass dimensions for large wildlife should be no smaller than 14 ft×14 ft and should include natural substratum inverts. Rail corridors have four characteristics that minimize adverse environmental impacts. The railbed is dry, ballast fillters runoff, there is little runoff beyond the toe of slope, and drainage ditches serve to control sheet flow and erosion, sediment movement, and uncontrolled channel flow. Rail corridors usually occupy smaller land areas because they are narrower and are more feasible to elevate so as to allow free movement of wildlife across the corridor. © 1993 Springer-Verlag New York Inc.
13 citations (Crossref) [2023-10-31]
Keywords: Environmental impacts; Habitat fragmentation; High-speed rail (HSR); animal; corridor; dept.bio; environmental impact assessment; forest; habitat fragmentation; note; railway; siting; species; united states; wildlife